Mechanics of Rotor Spinning Machines - Elhawary, Prof. Dr. Eng. Ibrahim Abdou (Taylor and Francis, 2017)
"This book explores the mechanics of rotor spinning machines. It discusses the open-end spinning machine rotor's vibrations and bearings as well as the kinematics of the rotor's drive as individual drive or central drive, both as a reducing drive and multiplying drive. It examines explanations for the rotor's power requirements through different techniques such as Shirley institute (UK) and Zurich Federal Institute. It also covers power distribution inside the machine, different mechanisms of the machine, and air flow inside the spinning machine."--Provided by publisher.